Metaheuristics for maritime operations - Homayouni, S. Mahdi; Fontes, Dalila B. M. M. ([London, UK] : ISTE, Ltd. : Wiley, 2018)
Metaheuristic Algorithms in Maritime Operations Optimization focuses on the seaside and port side problems regarding the maritime transportation. The book reviews and introduces the most important problems regarding the shipping network design, long-term and short-term scheduling and planning problems in both bulk and container shipping as well as liquid maritime transportation. Application of meta heuristic algorithm is important for these problems, as most of them are hard and time-consuming to be solved optimally.'
A Review of Maritime Operations -- Metaheuristic Algorithms -- Metaheuristics for Ship Operations -- Optimization of Seaside Operations -- Problems in Yard Operations -- Conclusion.
Includes bibliographical references and index.
Title from title details screen.
John Wiley and Sons
Keywords: Shipping -- Data processing; TRANSPORTATION -- Ships & Shipbuilding -- Pictorial; Shipping -- Data processing